Does Tax Planning and Deferred Tax Expense Affect Earnings Management? - Nofrivul Nofrivul; Elsa Fitri Amran; Widia Firmanola (Accounting Analysis Journal, 2022)
Purpose : To achieve high profits the company must have a competitive advantage compared to other companies, one of which is the ability to manage finances well, in order to ensure the company’s long-term viability, which is reflected in the amount of profit generated. This is what motivates managers to take deviations in the presentation and reporting of earnings information, which is called earnings management. The goal of this research is to determine the impact of tax planning and deferred tax expense on earnings management. Method : The study uses purposive sampling method and obtained 36 manufacturing companies for eight years of observation. The population used are manufacturing companies listed in Indonesian Stock Exchange (IDX) during the years 2013-2020. The data were tested using logistic regression. Findings : The result of this study indicated that tax planning has no effect on earnings management and deferred tax expense has effect on the probability of companies doing earnings management. While tax planning and deferred tax expense have a simultaneous effect on earnings management. Novelty : The research was conducted to determine the factors that influence the company to practice earnings management that is focused on tax planning and deferred tax expense. The earnings management measure used in this study is a dummy variable which implies the existence of a company policy to increase or decrease profits. Keywords : Tax Planning; Deferred Tax Expense; Earnings Management